Related Factors of Patent Ductus Arteriosus in Preterm Infants: A Systematic Review and Meta-Analysis - Liu, Chang; Zhu, Xingwang; Li, Dinggang; Shi, Yuan (Frontiers in Pediatrics, 2021)
Background: Patent ductus arteriosus (PDA) is a dramatically harmful disease in the neonatal period, in particular common in preterm infants, and our study was to determine related factors of PDA in preterm infants. Methods: A comprehensive literature review was conducted in PubMed, EMBASE and Web of Science. The pooled odds ratio (OR) and standard mean difference (SMD) were calculated to compare dichotomous and continuous variables, respectively. In addition, we also assessed the heterogeneity and publication bias and carried out sensitivity analysis for each related factor. Results: We included 45 studies with 87419 individuals. After the primary analysis and a series of adjustments, results showed chorioamnionitis, lower gestational age, lower birth weight, bronchopulmonary dysplasia, intraventricular hemorrhage, necrotizing enterocolitis, respiratory distress syndrome, sepsis, surfactant treatment, ventilation and lower platelet count had a positive correlation with PDA, while small for gestational age decreased the incidence of PDA in preterm infants. Besides, premature rupture of membranes, preeclampsia, antenatal steroids, male gender, mean platelet volume, platelet distribution width were found to have no statistically significant relationship with PDA. Conclusion: Preterm infants with more immature characteristics generally have a higher likelihood to develop PDA. The prevention, diagnosis and management of PDA may depend on these results and effective measures can be taken accordingly.